Study of iron impurity behaviour in the ADITYA tokamak. (26th June 2019) - Patel, S.; Srivastava, A.K.; Chowdhuri, M.B.; Manchanda, R.; Bhattacharya, A.; Raval, J.V.; Nagora, U.; Atrey, P.K.; Tanna, R.L.; Ghosh, J.
Abstract: Iron (Fe) impurity behaviour in ADITYA tokamak plasma has been studied using Fe spectral line emissions in the vacuum ultra violet (VUV) wavelength range. A VUV survey spectrometer has been utilized to record spectral lines at 28.41 nm from Fe 14+ , and 33.54 nm and 36.08 nm from Fe 15+ . It has been observed that the intensities of the Fe emissions decrease with an increase in plasma electron density. The observed emission and the intensity ratio of Fe 14+ and Fe 15+ ions from two discharges having relatively low and high plasma density are modelled using an impurity transport code. It is found that the observed data could be modelled using the same ratio of the convective velocity to the diffusion coefficient D profile, but with two different Fe concentrations. The ratio varies from the value of − 0.22 m −1 at the plasma normalized radius to a maximum value of − 0.35 m −1 at . The obtained diffusion coefficient value at the plasma core region is explained in terms of neo-classical transport, indicating that Fe impurity transport follows the same behaviour in the core plasma of the ADITYA tokamak.